SORCIS Model: Social Media Marketing Dimensions, Consumer Decision-Making Styles, and Purchase Intention - Bülbül, Nihal; Çayırağası, Filiz; Efendioglu, Ibrahim Halil (Mercados y Negocios, 2026)
This study examines purchase intention in digital marketplaces by integrating social media marketing (SMM) dimensions with Consumer Style Inventory (CSI) decision-making styles through the SORCIS framework. The results obtained from marketplace buyers in Türkiye were analyzed using structural equation modeling. Interaction, informativeness, personalization, trendiness, and electronic word-of-mouth (eWOM) each show positive and significant effects on purchase intention. Among CSI styles, brand consciousness, fashion or novelty consciousness, and website content consciousness are substantial predictors, whereas other styles are not. Theoretically, the study positions CSI styles as enduring organismic factors within the S–O–R structure, explaining why similar SMM cues yield heterogeneous intentions and clarifying the role of content quality and transparency in interface-parity environments. Managerially, the results highlight the importance of informative content, responsible personalization, and community-based interaction.